A Case of Primary Submandibular Gland Oncocytic Carcinoma. (11th September 2013) - Tokashiki, Kunihiko; Tsukahara, Kiyoaki; Motohashi, Ray; Nakamura, Kazuhiro; Suzuki, Mamoru
Abstract : Primary submandibular gland oncocytic carcinoma is a rare pathology, with only 10 cases being reported to date. We encountered a case of primary submandibular gland oncocytic carcinoma and report it herein. The patient was a 69-year-old man who came to our hospital with right submandibular cancer as the main complaint. Based on the results of computed tomography and magnetic resonance imaging, submandibular gland tumor was diagnosed. Preoperative cytodiagnosis suggested class III oncocytic carcinoma. Resection of the right submandibular tumor was performed along with right neck dissection. Postoperative histopathological diagnosis was oncocytic carcinoma. As of 3 years following surgery, no recurrence has been identified.